Rotator Cuff and Subacromial Pathology - Yablon, Corrie M.; Jacobson, Jon A. (Seminars in Musculoskeletal Radiology, 2015)
Both MRI and ultrasound (US) demonstrate equivalent accuracy in the evaluation of the rotator cuff. Both modalities have their advantages, disadvantages, and pitfalls. Radiography is an important complementary modality in that it can demonstrate occult sources of shoulder pain. MRI is recommended for the evaluation of shoulder pain in patients < 40 years of age because labral pathology is frequently identified. However, in patients > 40 years, US should be the first-line modality because the incidence of rotator cuff pathology increases with age. US is useful to guide procedures such as subacromial injection and calcific tendinosis lavage. Radiologists should be knowledgeable of both MRI and US of the shoulder to tailor these examinations to the specific needs of their patients.
Keywords: ultrasound of rotator cuff tears; MRI of rotator cuff tears; subacromial pathology; calcific tendinosis